(untitled) (Global Journal of Medical Research, 2021)
Background: There is abundant and even confusing information in the available literature concerning the role of internal limiting membrane (ILM) removal in macular conditions secondary to non-complicated macula-off rhegmatogenous retinal detachment (RRD) repair. This retrospective, multicenter, long-term study aimed to analyze the incidence of epiretinal membrane (ERM) proliferation and other surgical complications and to compare the postoperative microstructural and multimodal imaging findings and correlate them with the final postoperative best-corrected visual acuity (BCVA) in selected eyes.